Cinema e educação : um olhar para as práticas corporais de aventura - Santos, Karine dos Anjos (2023)
Physical Education, as a school component, should contribute to the humanized education of students, contributing to the perception of different themes and contexts. For this, the diversification of languages and ways of working in the classroom is necessary. Thus, we emphasize that the use of films, in this component, opens the way for dialogue between teachers and students, who can interact based on their perceptions of the world. With this, cinema expands the possibilities of working in Physical Education classes, which traditionally deal with body aesthetics. Therefore, we raise the following question: what are the possibilities of working with adventure body practices, seeking the relationship between the body and education through the language of cinema? From this questioning, which considers cinema as a human cultural practice, the general objective of this study was to analyze how the corporal practices of adventure, through cinema, potentiate school education. The relevance of this work is to carry out an education that associates bodily practices and cinema as a possibility of pedagogical practice. In this way, we list aspects of the film that support a conception of education rooted in a historical-social context. In this way, we selected two films “Soul Surfer – Coragem de viver” and “Uma Skater Radical”. From the first film we explored surfing and from the second, skateboarding, such practices were chosen because they are body practices in different environments (body practice of adventure in nature and in the city) which encompasses the types of Body Practices of Adventure presented in the “Base Nacional Comum Curricular” of Brazil. Methodologically, the study is of a qualitative nature, the method used was thematic analysis, in our case, we focused on the scenes of the films that are linked to the corporal practices of adventure, specifically those that contemplate the use of safety equipment, as well as those that brought about the realization of the fundamental movements of sports. The analysis also considers the humanized dimension that cinema provides with special attention to socioeconomic differences, the correlation of man and the nature and gender issue that films present. In this sense, we explored adventure corporal practices and cinema, as a way of expanding the possibilities of working in the classroom, since the school does not always provide structure for the teacher to explore the most varied corporal practices in the school environment.